2018
DOI: 10.3390/ijerph15051033
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Smoke Induces and Alters Immune Responses in the Lung Triggering Inflammation, Allergy, Asthma and Other Lung Diseases: A Mechanistic Review

Abstract: Many studies have been undertaken to reveal how tobacco smoke skews immune responses contributing to the development of chronic obstructive pulmonary disease (COPD) and other lung diseases. Recently, environmental tobacco smoke (ETS) has been linked with asthma and allergic diseases in children. This review presents the most actual knowledge on exact molecular mechanisms responsible for the skewed inflammatory profile that aggravates inflammation, promotes infections, induces tissue damage, and may promote the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
424
1
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 471 publications
(464 citation statements)
references
References 296 publications
(350 reference statements)
22
424
1
17
Order By: Relevance
“…Exposure to cigarette smoke alters immune mechanisms involved in allergic disease. As with traffic-related diesel pollution, AMs from smokers displayed reduced phagocytic abilities impairing both pathogen clearance from the lungs and removal of dead cells (178,179). Exposure to cigarette smoke increased production of IFN-γ and IL-17A by T cells in murine lungs, and recruitment of AMs, neutrophils, and γδT cells, a major source of IL-17A (180).…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to cigarette smoke alters immune mechanisms involved in allergic disease. As with traffic-related diesel pollution, AMs from smokers displayed reduced phagocytic abilities impairing both pathogen clearance from the lungs and removal of dead cells (178,179). Exposure to cigarette smoke increased production of IFN-γ and IL-17A by T cells in murine lungs, and recruitment of AMs, neutrophils, and γδT cells, a major source of IL-17A (180).…”
Section: Resultsmentioning
confidence: 99%
“…Many previous reports have revealed that CS could augment allergic inflammation (Botelho et al, 2011;Saulyte et al, 2014;Strzelak et al, 2018); however, chronic smoking exerts a protective effect on allergic sensitization to some aeroallergens and prevents allergic diseases protecting against pollinosis (Hjern et al, 2001;Sopori, 2002;Nagata et al, 2008;Monico et al, 2019). Various components of CS suppress the Th2 cell response, which plays an important role in IgE production and in the development of immediate hypersensitivity (Ozaki et al, 2010), although the mechanism by which CS protects against allergic sensitization has not been well clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, CS reportedly increases nasal allergic responses with concomitant increase in the serum immunoglobin E (IgE) level and production of interleukin-5 (IL-5) (Oryszczyn et al, 2000;Saulyte et al, 2014;Kim et al, 2017). In addition, CS directly affects the epithelial cells and results in increased permeability, mucus overproduction, increased release of proinflammatory cytokines and chemokines, enhanced recruitment of neutrophils, and disturbed lymphocyte balance toward T helper type 2 (Th2) cells (Strzelak et al, 2018). Recently, smoking has been recognized as a cause of acute eosinophilic pneumonia (AEP), which can occur within a few weeks or months of initiating smoking or even as a result of passive smoking exposure (De Giacomi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced growth of the child accompanied by delayed lung development, a higher premature birth rate, and more complications at birth contribute to increased asthma risk in children with prenatal exposure to cigarette smoke. Immunological mechanisms involve impaired Th1-type responses with a shift to Th2 immunity together with enhanced secretion of proinflammatory cytokine IL-17A by NK, NKT, and γδ T cells induced by exposure to cigarette smoke [68]. Accompanied by increased oxidative stress and imbalanced compensatory antioxidants, enhanced inflammation with increased expression of IL-8, IL-6, and TNF-α results in chronic mucosal inflammation.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Accompanied by increased oxidative stress and imbalanced compensatory antioxidants, enhanced inflammation with increased expression of IL-8, IL-6, and TNF-α results in chronic mucosal inflammation. Moreover, mucus overproduction, excessive recruitment of macrophages and neutrophils, and increased permeability of epithelial cells are reported consequences of paternal smoking [68].…”
Section: Environmental Factorsmentioning
confidence: 99%